TIPS-tetracene- and TIPS-pentacene-annulated poly(norbornadiene)s: synthesis and properties - Porz, Michael; Paulus, Fabian; Höfle, Stefan; Lutz, Tobias; Lemmer, Uli; Colsmann, Alexander; Bunz, Uwe H. F. (Macromolecular rapid communications, 2013)
The synthesis of tetracene- and pentacene-annulated norbornadienes, formed through the Diels-Alder reaction of a dehydroacene with cyclopentadiene is reported. Ring-opening metathesis polymerization (ROMP) leads to polymers that are investigated with respect to their physical, optical, and electronic properties by gel permeation chromatography (GPC), UV-vis spectroscopy, and cyclic voltammetry. The pentacene-containing polymer P1 is successfully integrated into an organic field-effect transistor (OFET); the tetracene-containing polymer P2 is integrated into an organic light-emitting diode (OLED).